2011
DOI: 10.1103/physrevlett.107.214301
|View full text |Cite
|
Sign up to set email alerts
|

Ear Deformations Give Bats a Physical Mechanism for Fast Adaptation of Ultrasonic Beam Patterns

Abstract: A large number of mammals, including humans, have intricate outer ear shapes that diffract incoming sound in a direction-and frequency-specific manner. Through this physical process, the outer ear shapes encode sound-source information into the sensory signals from each ear. Our results show that horseshoe bats could dynamically control these diffraction processes through fast nonrigid ear deformations. The bats' ear shapes can alter between extreme configurations in about 100 ms and thereby change their acous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 24 publications
5
85
0
Order By: Relevance
“…By using their unique sound focusing structures, odontocetes can optimize the energy impinging on a target, which would result in increased target detection, discrimination and overall foraging success. Anatomical adaptation is common in many other animals and across sensory modalities (Estes, 1972;Forrester et al, 1996;Gao et al, 2011). Therefore, our proposed focusing mechanism for odontocetes is not unusual, but rather is consistent with adaptive sensory behavior clearly demonstrated in many other animal species.…”
Section: Discussionmentioning
confidence: 48%
“…By using their unique sound focusing structures, odontocetes can optimize the energy impinging on a target, which would result in increased target detection, discrimination and overall foraging success. Anatomical adaptation is common in many other animals and across sensory modalities (Estes, 1972;Forrester et al, 1996;Gao et al, 2011). Therefore, our proposed focusing mechanism for odontocetes is not unusual, but rather is consistent with adaptive sensory behavior clearly demonstrated in many other animal species.…”
Section: Discussionmentioning
confidence: 48%
“…In bats, for example, the movement of the ears is fast and unpredictable, and is of special importance because of the bats' superior localization ability. Researchers have previously used high-speed video to capture this movement (Gao et al, 2011), but have not benefited from automated detection of events. Similarly, the method can be used to analyze interactions between cleaner fish and their clients (Bshary and Grutter, 2002;Bshary and Würth, 2001), which hitherto required laborious processing of videos and may be strongly biased by the subjectivity of the observer.…”
Section: Discussionmentioning
confidence: 99%
“…These shape changes are driven by specialized musculatures (Schneider and Möhres 1960;Schneider 1961;Göbbel 2002) and are known to occur during pulse emission (for the noseleaf (Feng et al2012;He et al 2015)) or echo reception (for the pinnae (Yin et al 2015)). Noseleaf and pinna motions are fast and occur on a similar time scale as the durations of the biosonar pulses and echoes (Gao et al 2011;Feng et al 2012;He et al 2015). Hence, these motions could change the acoustic characteristics of the biosonar emission and reception during a single pulse or a single echo.…”
Section: Dynamic Information Encoding: Noseleaf and Pinna Motionsmentioning
confidence: 99%
“…Hence, these motions could change the acoustic characteristics of the biosonar emission and reception during a single pulse or a single echo. Indeed, such changes have been predicted by numerical analysis (Gao et al 2011;He et al 2015) and demonstrated with biomimetic physical prototypes Fu et al 2016). Time variant acoustic characteristics would allow the bats to sense their environments through "multiple views" and hence could enhance the quantity -and perhaps also the quality -of the sensory information available to the animals.…”
Section: Dynamic Information Encoding: Noseleaf and Pinna Motionsmentioning
confidence: 99%